2015
DOI: 10.3747/co.22.2660
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1/2 Population Screening: Embracing the Benefits

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…[15][16][17] Because of the higher carrier frequency of three known BRCA founder mutations in the AJ population, the notion of offering them screening for these mutations has been suggested over many years. 5,[18][19][20] In 2008, in a free population screening program conducted by Steven Narod and colleagues in Canada, 2,080 unselected Jewish women were tested for the founder mutations. 21 Twenty-two new carriers were identified, only 10 of whom would have met the Canadian BRCA testing guidelines in place at that time.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] Because of the higher carrier frequency of three known BRCA founder mutations in the AJ population, the notion of offering them screening for these mutations has been suggested over many years. 5,[18][19][20] In 2008, in a free population screening program conducted by Steven Narod and colleagues in Canada, 2,080 unselected Jewish women were tested for the founder mutations. 21 Twenty-two new carriers were identified, only 10 of whom would have met the Canadian BRCA testing guidelines in place at that time.…”
Section: Resultsmentioning
confidence: 99%
“…Those seeking testing are often required to pay out-of-pocket to test through their healthcare provider or a direct-to-consumer testing company. Some genetics professionals have suggested that all AJ individuals be offered BRCA testing, regardless of their personal and family histories of cancer [18,19]. A 2010 community-wide BRCA testing initiative in Toronto [20] and a similar 2015 initiative in New York City [21] were successful at identifying low-risk AJ individuals with BRCA mutations and supported the notion that a greater number of mutation carriers will be detected if testing criteria are expanded to include anyone of AJ ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…Age is an important criteria for screening, but calls for population based preventive genomic screening programs 15 17 , 19 do not mention whether upper age should be a consideration in developing such programs. Questions remain whether such programs will employ upper age limits, as for other clinical screenings, on the assumption that older individuals would not benefit.…”
Section: Introductionmentioning
confidence: 99%